Sustainable stormwater management: Appreciation of Low Impact Development Techniques (LID) for southern Brazilian municipalities - Marostica, Sara Desiree; Silveira, André Luiz Lopes da Silveira (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
This article aims to explore the perception of Low Impact Development - LID techniques by municipal technicians. From the mapping of low-impact techniques (LID) for controlling urban flooding in affected areas, we sought to investigate responses from technicians from southern Brazilian municipalities to the perspective of sustainable landscapes and practices in rainwater management, as research focusing knowledge of LID projects implemented in urban areas. This study provides empirical insights into municipal technicians’ perception of urban LID practices by studying user responses to ten applied techniques, eight with LID design and two with conventional urban drainage design. The majority of the respondents, although expressing some limited knowledge of stormwater, manifested their appreciation of LID techniques. This finding implies that the implementation of new LID systems can result in positive attitudes by policymakers and urban planners for developing stormwater management programs, the findings that enrich the technical experience of projects accomplish in southern Brazilian municipalities.